Cinema Africa 2023 - A conversation with Cédric Ido (Cinema Africa 2023, 2023)
As part of the Cinema Africa festival 2023, director and screenwriter Cédric Ido was a guest of the Africa Multiple Cluster of Excellence in Bayreuth. In this interview, he talks with Dr. Maroua El Nag-gare and Jelena Mijajlovic about his film “La Gravité” which he presented at the film festival. The movie is about two brothers living in a ghetto eager to do anything for their freedom. When an unprecedented alignment of planets seemingly impacts earth’s gravity and upsets the balance in the ghetto, they find themselves in an unceasing fight between old and new generations.